Foot pain in a high school girls` basketball player - Jacobs, D.; Ullery, L. R.; Smoot, M. K. (Journal of Athletic Training, 2019)
Background: A 14-yearold female basketball player (height: 5ft 2in± 157.48cms, mass: 102±46.2kgs) reports to the Athletic Trainer, complaining of left foot pain during and after activity. She had been involved with basketball activities for 5 weeks. There was no acute injury to her left foot, the onset of pain was insidious, and was gradually worsening. The pain was located over the second metatarsal, and was reported as an 8-10 on numeric pain scale, worse with weight-bearing activities, and described as sharp and achy. The evaluation revealed edema over her forefoot, no ecychomyosis, neurologically intact, and strong distal pulses. She also had full strength and ROM of the foot, ankle and toes, which did not cause her pain. She had a prior history of Freidberg's infraction on her right foot three years earlier. The Athletic Trainer placed her in short boot and crutches, and referred her to the sports medicine clinic. Differential Diagnosis: Stress fracture, Metatarsalgia, Morton' neuroma, Freiberg's Disease. Treatment: X-rays ruled out a stress fracture, but revealed a flattening of the second metatarsal head. No additional imaging was ordered, given the deformity present on the x-ray. The patient was advised to continue to wear the boot with a foam metatarsal arch support and crutches. In addition, she was prescribed an NSAID for the in flammation and pain. Custom orthotics were ordered with an empty space in the metarsal area to off load the second metatarsal. She was to report back the clinic if the pain did not subside. The patient continued to work on ROM and strength for three weeks with the Athletic Trainer to reduce pain and swelling. During this time, she began weight- bearing activities and gradually, weaned out of the boot. By 6 weeks, she was able to participate in basketball with her orthotics in her shoes. She was able to complete the season without further problems of the second and third metatarsals. Most only occur in a single metarsal and only 10% of the injuries were reported bilaterally. Uniqueness: Freiberg's disease is a rare condition where avascular necrosis causes osteochrondosis to occur. It is commonly found in the second metatarsal head due to the length of the bone. The third metarsal head is the next common site, but can occur in any of the five metatarsals. This injury is subdivided into five categories based on the x-ray presentation. At first, the injury was found to be an infraction since the cause was thought to be a traumatic mechanism of injury. However, there has not been a consensus of the cause of Freiberg's disease. The disease has a commonality with other osteochondrosis conditions because of the growth disruption of the epiphysis or apophysis in growing bones. Usually this injury occurs in active females ages 10-17, with a ratio of 1:3 male to female. Freiburg's disease has been found in ages as young as 8 and as old as 77. Multiple factors are reported to cause this injury including repetitive trauma, anatomical predisposition, shoe wear, low blood supply to the area, and lack of mobility of the second and third metatarsals. Most only occur in a single metarsal and only 10% of the injuries were reported bilaterally. Conclusion: Frieberg's disease or infraction is an uncommon injury, and can be caused by multiple factors. Bilateral involvement is rare. All classifications can be treated conservatively, and those that do not heal with conservative treatment may require surgery. When evaluating foot injuries, clinicians working with adolescent athletes should be aware of the various boney injuries possible and follow their current treatment plan to obtain x-rays if bone pain continued. The patient was able to return to basketball with conservative treatment wearing bilateral orthotics in her shoes, without any further complaints.